Intervención fisioterapéutica en paciente de 20 años de edad con rotura de ligamento colateral que acude al área de rehabilitación física del Hospital General Martín Icaza del Cantón Babahoyo. - Tapia Avilez, Iván Jossue (2025)
Medial collateral ligament injuries are two to three times more common than posterior cruciate ligament injuries. The objective of this case is to diagnose a 20-year-old male patient who, after being diagnosed with a rupture of the medial collateral ligament in the right knee and undergoing surgical treatment, presents to the physiotherapy department with significant functional limitations. The main complaints at the beginning of the therapeutic process include constant moderate pain, restriction in full knee extension, and a sensation of instability while walking, which highlights the need for a specialized, gradual, and structured intervention. Addressing this case study emphasizes the importance of implementing a comprehensive physiotherapeutic treatment, organized in stages and tailored to the patient’s individual needs. The advantage of conducting this study lies in producing tangible evidence of the effectiveness of the therapeutic strategies applied, allowing the assessment not only of the patient’s physical recovery but also of his reintegration into daily and sports activities. This analysis provides a relevant contribution to enhancing the practice of physiotherapy in public hospital settings, such as the General Hospital Martín Icaza, through monitoring and follow-up.